Legal Protection of Intellectual Property Rights in Indonesia for SME Performance - Sukania, I Wayan; Agustinus Purna Irawan; Fransisca Iriani Roesmala Dewi; Esanov Azamat Esirgapovich (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2025)
Small and Medium Enterprises (SMEs) play an important role in economic growth, job creation, and driving innovation. However, the competitiveness of SMEs is often hampered by weak protection of intellectual capital assets, particularly in aspects of intellectual property related to SME trademarks. This article examines the urgency of establishing a comprehensive legal framework to protect intellectual capital assets, specifically in aspects of intellectual property related to SME trademarks, as a strategic effort to promote innovation and improve SME performance. The research method used is normative legal research with a legislative, conceptual, and comparative approach to the practice of intellectual property law protection with South Korea and Singapore. The findings demonstrate three central points. First, Indonesian culinary SMEs actively confront major obstacles in implementing legal protection for intellectual capital assets, particularly intellectual property. Complex registration bureaucracy, high administrative costs, weak law enforcement, and low literacy among business owners directly hinder their capacity to innovate and compete. Second, comparisons with South Korea and Singapore illustrate that states can significantly enhance SME competitiveness by integrating efficient intellectual property protection systems with economic incentives and by cultivating a strong legal culture. Third, Indonesia must design and implement a responsive, inclusive, and adaptable model of intellectual capital protection, particularly in the field of intellectual property. Policymakers can achieve this goal by simplifying regulations, strengthening regional institutions, and advancing public education. Through these measures, intellectual property will operate not merely as a legal safeguard but as a strategic asset that stimulates innovation, broadens access to financing, and empowers culinary SMEs to become a driving force in building a globally competitive creative economy.